MEDIA CONTRIBUTION TO TOURISM DEVELOPMENT AND INCOME INEQUALITY: IMPLICATIONS AND CHALLENGES - Fitrianti, Nida; Padma Hanuun, Nazhira Nindya; Fatmasari, Raden Roro (KRIEZ ACADEMY : Journal of development and community service, 2024)
The role of the media in the tourism industry has been the subject of increasing attention in recent years. Media has the ability to shape people's perceptions of tourism destinations, promote travel trends, and influence income distribution among local communities in tourism destinations. However, the media's impact is not always evenly distributed, and often impacts problems such as over-tourism and income inequality. This study explores the implications of media coverage for tourism, focusing on two main aspects: the impact of media promotion on revenues in highly visited and less popular tourism destinations, and the role of the media in promoting sustainable and responsible tourism. Data from various tourism industry studies and reports are used to evaluate trends and find appropriate solutions to overcome the challenges faced. The results show that intensive media coverage of popular tourism destinations tends to increase income, but can also lead to significant income inequality between affected and unaffected destinations. Meanwhile, the media can also be an effective tool for promoting sustainable tourism by conveying appropriate information, strengthening awareness of the importance of environmental and cultural preservation, and promoting lesser-known destinations. With collaboration between the government, the tourism industry, and the media, these efforts can help reduce the problem of over-tourism, increase tourism sustainability, and ensure equitable benefits for local communities in various tourism destinations.